2020
DOI: 10.18632/aging.103069
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of outcome after aneurysmal subarachnoid hemorrhage

Abstract: In this observational study, we analyzed and described the dynamics of the outcome after aneurysmal subarachnoid hemorrhage (SAH) in a collective of 203 cases. We detected a significant improvement of the mean aggregate modified Rankin Score (mRS) in every time interval from discharge to 6 months and up to 1 year. Every forth to fifth patient with potential of recovery (mRS 1-5) at discharge improved by 1 mRS point in the time interval from 6 month to 1 year (22.6%). Patients with mRS 3 at discharge had a rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
3
9
1
Order By: Relevance
“…Namely, mild neurological grade on admission was the factors improving outcomes. Hammer et al reported that WFNS grade I or II were signi cant factors of improvement from discharge to 6 months after onset (WFNS I-II vs. III-V: OR 4.77; 95% CI 1.51-15.05; p = 0.0077) in the multivariate analysis, [5] which supports our results.…”
Section: The Factors For Improvement Of Mrs Scores After Dischargesupporting
confidence: 91%
See 4 more Smart Citations
“…Namely, mild neurological grade on admission was the factors improving outcomes. Hammer et al reported that WFNS grade I or II were signi cant factors of improvement from discharge to 6 months after onset (WFNS I-II vs. III-V: OR 4.77; 95% CI 1.51-15.05; p = 0.0077) in the multivariate analysis, [5] which supports our results.…”
Section: The Factors For Improvement Of Mrs Scores After Dischargesupporting
confidence: 91%
“…The changes in the prevalence of good outcome (mRS score: 0-2 or Glasgow Outcome Score: 4-5) between discharge and the last follow-up ranged from 8.4-55.2%. [2,5,18,24,25,30] The prevalence of improvement of mRS scores in total cases between discharge and at 6 months ranged from 57.4-61.0%, [5,30] and the prevalence of declined mRS scores during the same period was 17.0%. [30]…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations